The Nigerian maladapted financial system : reforming tasks and development dilemma - Ojo, Ade T. (Ota, Nigeria: Professor Ade T. Ojo, 2010)
The book depicts and analyses Nigeria's maladapted financial system and many of Africa's financial systems, that have missed and continue to miss the several golden opportunities which could have effectively mobilized Nigeria's huge petroleum resources for industrial investment, in a manner that could have boosted production of goods and services as well as the nation's industrial transformation and economic development. The book is expected to highlight the deplorable situation as well as make the government, financial authorities and other stakeholders in the finance industry device better and more effective strategies that would ensure that the financial system is appropriately re-positioned to perform its developmental functions in desirable ways.
Includes index.
rpm 04/09/13
Loans
Keywords: Economic reforms -- Nigeria; Financial system -- Nigeria